Pengaruh Model Jarak Tanam Jajar Legowo terhadap Pertumbuhan dan Hasil Padi (Oryza sativa) Varietas IPB 3S - Isromi Kurniawan; Lia Kristina; Ruly Awiyantini (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Efforts to increase agricultural production can be made by using new high-yielding varieties and modifications to plant spacing. IPB 3S rice variety is a new type of rice variety with a yield potential of 7-8 tons/hectare and panicle length, grain weight per panicle, and higher grain weight than the Ciherang variety. This study is an experimental study using a Randomized Block Design (RAK) consisting of three treatments plus one control (without treatment) with three replications. The data obtained were analyzed by analysis of variance using the F test, according to the experimental design used, then tested with Duncan's Multiple Range Test (DMRT) or Duncan's Test to determine the difference between each treatment with an error rate of 5%. The treatments in this study were: P0 (Distance for Planting Tiles), P1 (Distance for Planting Jajar Legowo 2:1), P2 (Distance for Planting Jajar Legowo 3:1); and P3 (Jajar Legowo Planting Distance 4:1). The results showed that the plant spacing treatment of jajar legowo did not affect plant height and the number of tillers, except for the number of tillers at 55 DAP. However, it significantly affects panicle length and dry grain yield. The 2:1 row spacing of legowo indicates the highest yield.